2015
DOI: 10.1111/cch.12235
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders among women, social circumstances and toddler growth in rural Vietnam: a population‐based prospective study

Abstract: Maternal post-natal CMD are associated with child growth measured by LAZ in this resource-constrained setting. Social adversities affect child growth indirectly through increasing the risk of maternal CMD. Interventions to reduce stunting in low-income settings may need to address maternal CMD and social adversities in order to improve impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…The adverse effects of maternal perinatal CMD on early childhood growth were also established. 43 When other factors were controlled, children whose mothers experienced CMD in late pregnancy or early postpartum had lower length-for-age Z score at 15 months of age (−0.15, 95% CI −0.28 to −0.05). It is the first study worldwide to show that father’s behaviour is also relevant to child growth as a more hostile marital relationship was associated indirectly with lower toddler length-for-age Z scores via maternal CMD.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects of maternal perinatal CMD on early childhood growth were also established. 43 When other factors were controlled, children whose mothers experienced CMD in late pregnancy or early postpartum had lower length-for-age Z score at 15 months of age (−0.15, 95% CI −0.28 to −0.05). It is the first study worldwide to show that father’s behaviour is also relevant to child growth as a more hostile marital relationship was associated indirectly with lower toddler length-for-age Z scores via maternal CMD.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000 we have generated epidemiological evidence about the mental health of women in rural Vietnam. Four rigorous studies, reported in six papers, examined the prevalence and intermediary determinants, but not the socioeconomic and political context, of antenatal CMDs [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the prevalence of depression is greater among women, an epidemiological finding that can potentially be explained by genetic and environmental risks and their interaction [ 2 4 ]. Women living in low and middle income countries (LMICs) are at increased risk for common mental disorders including depression, in part due to the high prevalence of poverty-related stressors that disproportionately affect women, such as food insecurity, limited education, financial hardship, intimate partner violence, and high fertility rates [ 5 11 ]. Furthermore, contextual effects, including living in a region without geographic proximity to health care and/or lacking access to daily necessities have been shown to contribute to depression [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%